Should helicopters have a hoist or 'long-line' capability to perform mountain rescue in the UK?. Issue 1 (28th October 2010) - Ellerton, John; Gilbert, Hannah
Abstract : Objectives: To determine how far mountain rescue casualties in the UK have to be carried and the impact of adding a hoist or 'long-line' to helicopters operating in this environment. Design: Retrospective analysis of mountain rescue incidents. Setting: Pre-hospital, mountain rescue service based in Patterdale, English Lake District. Participants: Casualties between 1 January 2006 and 31 December 2008 that required stretcher evacuation. Casualties directly accessible by a road ambulance were excluded. Main outcome: The horizontal and vertical distance of the evacuation route to an agreed helicopter-landing site, and its technical character. Direct access to the incident site by a helicopter with a hoist or long-line capability was determined. Results: 119 casualties were identified. The median horizontal and vertical evacuation distances were 250 m and −30 m respectively. The proposed manual carrying distances were ≤100 m in 33/119 (28%), between 101 and 400 m in 60/119 (50%) and >400 m in 26/119 (22%) of casualties. 13/119 (11%) casualties were in a position where direct access to the incident site would not have been possible with a helicopter equipped with a hoist or long-line. 31/119 (26%) casualties required a technical evacuation with the use of ropes. Conclusions: Using the criteria that all casualties requiring a technical rescue or >400 m evacuation route to an appropriate helicopter-landing site, 34% of casualties could have been rescued using a hoist or long-line with an expected reduction in the pre-hospital time. Helicopters working in UK mountain rescue should be equipped to international standards.